Keutamaan Menuntut Ilmu dalam Perspektif Islam di Kehidupan Modern : Tantangan, Peluang, dan Pengaruh Teknologi dalam Pembentukan Karakter di Era Digital - Zakiyatul Mardiya; Ainur Rofiq Sofa (Universitas Maritim AMNI Semarang, 2025)
The importance of seeking knowledge in Islam is emphasized as one of the means to achieve both worldly and eternal happiness. However, in the digital era, seeking knowledge faces new challenges and opportunities. This study examines the Islamic perspective on seeking knowledge in modern life, focusing on the challenges, opportunities, and the influence of technology on character development in the digital age. The main challenges include the overwhelming amount of information that may not always be of high quality, as well as the distractions brought by technology that can divert attention from the core purpose of education. On the other hand, the opportunities presented by the digital era include easy access to various knowledge sources through online platforms and more interactive and engaging learning methods. This research also identifies the influence of technology, such as social media and educational apps, in shaping an individual’s character through the dissemination of Islamic values that promote good morals. The findings show that although the challenges in the digital era are considerable, technology can be leveraged to enhance the pursuit of knowledge and ethical education when used wisely. Character development, in line with Islamic teachings, can still be achieved through the wise use of technology in seeking knowledge. This study recommends the integration of technological education and ethical education to shape a generation that is knowledgeable, morally upright, and ready to face the challenges of the modern world.